Miss Congeniality 2 : armed and fabulous - Pasquin, John (Warner Bros, 2005)
Sandra Bullock returns as Special Agent Gracie Hart in a funny, Fabulous Miss Congeniality follow-up. This time, she's the bureau's new celebrity face, making the rounds of talk shows (her heroics at the Miss United Staes Beauty Pageant made her too famous for field work). She also has a new partner (Regina King), an agent with anger management issues and a dim opinion of pampered Gracie. But when Gracie's friends (returning stars Heather Burns and William Shatner) are kidnapped, nothing can keep Special Agent GS13 out of the action. Look out world. The cover girls is going back undercover!